Studying the Structures of Relaxed and Fuzzy Interactions: The Diverse World of S100 Complexes - Ecsédi, Péter; Gógl, Gergő; Nyitray, László (Frontiers in Molecular Biosciences, 2021)
S100 proteins are small, dimeric, Ca2+-binding proteins of considerable interest due to their associations with cancer and rheumatic and neurodegenerative diseases. They control the functions of numerous proteins by forming protein–protein complexes with them. Several of these complexes were found to display “fuzzy” properties. Examining these highly flexible interactions, however, is a difficult task, especially from a structural biology point of view. Here, we summarize the available in vitro techniques that can be deployed to obtain structural information about these dynamic complexes. We also review the current state of knowledge about the structures of S100 complexes, focusing on their often-asymmetric nature.